Age and growth of the venus clam Gafrarium tumidum (Roding) from south-east coast of India - Jagadis, I; Rajagopal, S (Indian Journal of Fisheries, 2011)
Age and growth of the Venus clam Gafrarium tumidum was studied in detail employing four conventional methods and an electronic package ELEFAN – 1. The growth rate obtained by all the methods was more or less similar and comparable with one another. The clam reached a length of 24.4, 31.9 and 37.7 mm at the end of 1st, 2nd and 3rd year of its life. Growth rates of male and female clams were similar and observed to be faster in the first year and then tended to slow down with age. The life span of Gafrarium tumidum was estimated to be 3 years.